The hybrid personal cooling system (PCS) could effectively reduce the heat strain while exercising in a hot and moderate humid environment - Song, Wenfang; Wang, Faming (Ergonomics, 2016)
This study aimed to examine the effectiveness of a hybrid personal cooling system (PCS) in mitigating body heat stain while exercising in a hot environment. Eight subjects underwent two trials: PCS and CON (i.e. no cooling). All trials were conducted at an air temperature of 36 ± 0.5 °C and RH = 59 ± 5%. The key findings demonstrated that the PCS could significantly reduce the core temperature, mean skin temperature, heart rate and physiological strain index during both exercise and recovery periods (p < 0.05). Subjective perceptions were also significantly alleviated in PCS at the end of the exercise and during the recovery (p < 0.05). Besides, the PCS could also bring remarkable benefits in lowering local skin temperatures and in improving perceptual sensations in both upper and lower body during both exercise and recovery periods (p < 0.05). It was thus concluded that the hybrid PCS is effective in mitigating body heat strain while exercising in a hot environment. Practitioner Summary: In hot and humid environments, body heat dissipation through sweating is greatly restricted. Our newly developed hybrid PCS could effectively alleviate heat strain while exercising in hot environments. The findings contribute to the body of knowledge in improving the health and well-being of sportsmen while exercising in hot environments.